2014
DOI: 10.1088/0004-637x/784/1/72
|View full text |Cite
|
Sign up to set email alerts
|

A Non-Radial Oscillation Mode in an Accreting Millisecond Pulsar?

Abstract: We present results of targeted searches for signatures of non-radial oscillation modes (such as r-and g-modes) in neutron stars using RXTE data from several accreting millisecond X-ray pulsars (AMXPs). We search for potentially coherent signals in the neutron star rest frame by first removing the phase delays associated with the star's binary motion and computing fast Fourier transform power spectra of continuous light curves with up to 2 30 time bins. We search a range of frequencies in which both r-and g-mod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 60 publications
(159 reference statements)
1
50
0
Order By: Relevance
“…This somewhat simple picture describing the r-mode instability window is inconsistent with observed spins and temperatures of lowmass X-ray binaries, implying the complete physical picture behind this mechanism is ill-understood (Ho, Andersson, & Haskell 2011;Haskell, Degenaar, & Ho 2012). Strohmayer & Mahmoodifar (2014) recently analysed Rossi X-ray Timing Explorer (RXTF) observations of the accreting millisecond pulsar XTE J1751-305, finding evidence for a coherent oscillation mode during outburst that they attributed to either an r-or g-mode (for which buoyancy is the restoring force). The r-mode interpretation is the most interesting in the context of gravitational wave emission; had the outburst occurred during the S5 LIGO run it would have been marginally observable (Andersson, Jones, & Ho 2014).…”
Section: Unstable Oscillation Modesmentioning
confidence: 96%
“…This somewhat simple picture describing the r-mode instability window is inconsistent with observed spins and temperatures of lowmass X-ray binaries, implying the complete physical picture behind this mechanism is ill-understood (Ho, Andersson, & Haskell 2011;Haskell, Degenaar, & Ho 2012). Strohmayer & Mahmoodifar (2014) recently analysed Rossi X-ray Timing Explorer (RXTF) observations of the accreting millisecond pulsar XTE J1751-305, finding evidence for a coherent oscillation mode during outburst that they attributed to either an r-or g-mode (for which buoyancy is the restoring force). The r-mode interpretation is the most interesting in the context of gravitational wave emission; had the outburst occurred during the S5 LIGO run it would have been marginally observable (Andersson, Jones, & Ho 2014).…”
Section: Unstable Oscillation Modesmentioning
confidence: 96%
“…There are, of course, issues to be resolved, especially concerning the dynamical role of the interior magnetic field in these systems [24]. A more indirect example comes from X-ray timing of fast spinning accreting neutron stars in Low-Mass X-ray Binaries [25,26]. The spin of these stars appears to be limited by some process.…”
Section: Introductionmentioning
confidence: 99%
“…Now we are in possession of the best estimate for the rmode frequency as a function of the stellar compactness, radius and angular velocity, and we can use it to estimate the compactness of the two stars XTE J1751-305 and 4U 1636-536 for which it was reported that a frequency compatible with an r-mode was detected. Strohmayer & Mahmoodifar (2014a) found an oscillation with a frequency of 0.5727597 times the spin frequency of 435 Hz in the 2002 discovery outburst of XTE J1751-305. An interpretation of this frequency as an r-mode therefore implies κ = 0.5727597.…”
Section: Numerical Results For Xte J1751-305 and 4u 1636-536mentioning
confidence: 98%
“…Their frequencies are tantalizingly close to the Newtonian estimate for the r-mode frequency of these stars. Strohmayer & Mahmoodifar (2014a) suggested that possible identifications of the observed frequency include rotationally modified g-modes or alternatively an inertial mode or core r-mode modified by the presence of a solid crust. However, the r-mode amplitude derived from the observed modulation amplitude would lead to a spindown rate too large to be consistent with the observations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation